Androgen replacement therapy for cancer‐related symptoms in male: result of prospective randomized trial (ARTFORM study). Issue 4 (24th May 2021) - Izumi, Kouji; Iwamoto, Hiroaki; Yaegashi, Hiroshi; Nohara, Takahiro; Shigehara, Kazuyoshi; Kadono, Yoshifumi; Nanjo, Shigeki; Yamada, Tadaaki; Ohtsubo, Koshiro; Yano, Seiji; Mizokami, Atsushi
Abstract: Background: Hypogonadism associated with cancer is reported to cause cachexia and a variety of physical and psychological symptoms. This study aims to evaluate whether androgen replacement therapy can improve cancer‐related symptoms in male advanced cancer patients. Methods: An investigator‐initiated, prospective, and randomized controlled study was conducted. Patients with low serum testosterone levels (total or free testosterone levels were <2.31 ng/mL or <11.8 pg/mL, respectively) were randomly assigned to the control or testosterone enanthate administration (testosterone group) groups. Testosterone enanthate was injected into the muscle tissue at a dose of 250 mg every 4 weeks (baseline, week 4, and week 8). Differences in quality of life questionnaires and cachexia‐related serum protein levels between groups were assessed. Results: This study enrolled and randomized 106 and 81 patients, respectively. Moreover, 41 and 40 patients were in the control and testosterone groups, respectively. Although no significant differences in the change of subscales and total scores in Functional Assessment of Anorexia/Cachexia Treatment were noted from the baseline between the two groups, the testosterone group showed a significantly better change in the 'unhappiness' item of the Edmonton Symptom Assessment System at week 12 compared with baseline versus the control group (−1.4 and 0.0 points, respectively; mean, P = 0.007). No significant differences exist in the change of serum interleukin‐6 and insulin‐like growth factor‐1 levels at week 12 from the baseline between the control and testosterone groups. Consequently, the testosterone group significantly inhibited the change in serum tumour necrotic factor‐α level at week 12 from the baseline compared with the control group (+0.4 and +0.1 pg/mL, respectively; mean, P = 0.005). Conclusions: Although testosterone enanthate did not improve most of the items in health‐related quality of life questionnaires, testosterone enanthate induced a significantly better change in the 'unhappiness' item at week 12 compared with the control. Testosterone enanthate may be a potential treatment option for male advanced cancer patients.